엄마 거북이 구하기: 직간접 감정유발 게임의 디자인 - 송병호; Song, Byoung-Ho (한국콘텐츠학회 논문지, 6(11), 2006)
To solve the reverse function problem of computer games criticized nowadays, the main fact to be concerned in design should be to make feelings of satisfaction during playing and solving the given situation in the game world. In this paper, a design to fulfill the feelings of satisfaction directly and indirectly, controlling playable characters to help another non-playable character in some sort of danger is explained. The requirements to do so is analyzed and the result of demonstration is also presented. 요즈음 논란이 되고 있는 컴퓨터 게임의 역기능을 해소하기 위해서는 게임 본연의 재미요소인 주어진 문제 해결을 통한 만족감 추구가 게임 디자인의 주 고려 요소가 되어야 한다. 본 논문에서는 위험에 빠진 플레이불가능 캐릭터를 플레이가능 캐릭터 조종을 통해 돕는 과정에서 직접 및 간접적인 경로로 감정이 유발되어 만족감을 충족시키는 게임을 디자인한 내용을 설명하였다. 이를 위하여 필요한 요건을 분석하였고 디자인 결과를 시연한 결과도 기술하였다.